Dilemma in diagnosis of pregnancy in didelphys uterus: a original case report - Sagar, Amrita; Sagar, Neeta; Dogra, Kusum (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Uterine didelphys is a congenital defect of female genital system that arises from abnormal embryological development of mullerian ducts. A 30-year-old female G4P3L3A0 at 9 weeks POG with uneventful previous three normal term delivery presented to gynae OPD of JPCH for medical termination of pregnancy and tubal ligation. On per speculum examination, cervix was found to be healthy and on per vaginal examination the uterus was parous size. Right adnexa were free and non-tender but left adnexal mass 4´4 cm felt which was non tender. USG findings was suggestive of live left ectopic pregnancy of 8wks with no free fluid. Patient underwent laparotomy. Per-op findings-two separate uterus with right fallopian tube attached to right uterus and left fallopian tube attached to left uterus. Left uterus was enlarged to 8 weeks. Right uterus was normal in size. Both right and left ovaries were normal. Patient wanted MTP with ligation, suction and evacuation were performed. B/L tubal ligation was done by modified Pomeroy’s method. The postoperative period was uneventful and on day -8 stitch was removed.